Odpowiedzi

2009-12-18T09:03:08+01:00
4(z-1)kwa+(2z+3)(3-2z)=-4z+1
4(zkwa-1)+6z-4zkwa+9-6z=-4z+1
4zkwa-4+6z-4zkwa+9-6z=-4z+1
4z=1-9+4
4z=-4
z=-1


(x+1)kwa=(x-1)kwa-2(x-4)
xkwa+1=xkwa-1-2x+8
2x=-1+8-1
2x=6/2
x=3
2009-12-18T09:08:33+01:00
4(z-1)do2+(2z+3)(3-2z)=4z+1
4zdo2-1+6z-4zdo2+9-6z=4z+1
8=4z+1
4z=-8+1
4z=-9/4
z=-9/4
z=-21/4


(x+1)do2=(x-1)do2-2(x-4)
xdo2+1=xdo2-1-2x+8
1=9-2x
2x=-1+9
2x=10/2
x=5
2009-12-18T09:10:00+01:00
^-kwadrat
/-kreska ulamkowa

a) 4(z-1)^ + (2z+3)(3-2z)= - 4z+1
4(z^-2z+1)+6z-4z^+9-6z = -4z+1
4z^-8z+4-4z^+9= -4z+1
-4z=-12 dzielimy obustronnie przez(-4)
z=3

b) (x+1)^=(x-1)^ -2(x-4)
x^ - 1 = x^ +1 -2x+8
2x=8
x= 4